Assessing the Urgency of Legal Certainty in the Provision of Health Services at Community Health Centers with Basic Emergency Obstetric and Neonatal Care Capacity in East Lombok Regency - Gusti Ayu Ratih Damayanti; Sukarno; Ahmad Rifai (Faculty of Law, Universitas Pekalongan, 2025)
Health facilities equipped with adequate infrastructure and competent healthcare personnel represent the most ideal setting for providing care during pregnancy, childbirth, the postpartum period, and the neonatal phase. Consequently, the availability of Community Health Centers (Puskesmas) capable of providing Basic Emergency Obstetric and Neonatal Care (PONED) is expected to contribute significantly to the reduction of maternal mortality (AKI) and infant mortality (AKB), particularly in East Lombok Regency. However, research findings indicate that the implementation of health services at Puskesmas capable of PONED in East Lombok Regency remains ineffective. Contributing factors include inadequate facilities and infrastructure, the limited number of healthcare personnel certified in PONED training, delays in updating assignment letters related to staff transfers (which affects their authority), and a lack of adequate evaluation and supervision in service delivery. Legal certainty in the implementation of health services at Puskesmas capable of PONED can be strengthened through several measures: (a) Regular evaluation and supervision of operational eligibility, formalized through official decrees; (b) Increased budget allocation for PONED training programs for healthcare workers; (c) Alignment of staff transfers with the conditions and needs of PONED-capable Puskesmas; and (d) The formulation and issuance of new regulations that provide comprehensive guidelines for health service delivery at PONED Puskesmas. These legal and operational enhancements are essential for ensuring quality and continuity in maternal and neonatal healthcare, which in turn supports broader public health goals in the region.